Workers Beneath the Floodgates: The Impact of Low-Wage Import Competition and Workers' Adjustment - Hâle Utar (Center for Economic Studies and ifo Institute (CESifo), 2016)
I analyze the impact of a low-wage trade shock on manufacturing workers in a high-wage country, Denmark, and how they adjust to the shock over a decade across all potential adjustment margins, in the labor market and outside. My research illustrates the importance of industry-specific human capital in trade adjustment and provides initial evidence of skill upgrading at the individual level as workers re-build lost human capital through education. Employing administrative person-level panel data matched with employer data for the period 1999 to 2010, I exploit the dismantling of import quotas on Chinese textile and clothing products in conjunction with China's accession to the WTO as a quasi-natural experiment and utilize within-industry heterogeneity in workers' exposure to this trade shock. Results show a negative and significant impact of the low-wage import shock on workers' future earnings and employment trajectories, which stems mainly from shortened employment at the firm that was exposed to the competition shock and subsequent difficulty in maintaining stable employment. While the service sector is the main absorber of all types of workers displaced by the import shock, recovery from the shock in service sector jobs varies greatly across workers depending on occupation, education and age. Less-educated, older and workers who had occupations with a high industry-specific skill content at the exposed firms had the worst adjustment experience. The results show that trade-induced adjustment costs are substantial and heterogeneous across workers. For some, challenges remain even after transitioning to full-time jobs outside of manufacturing, as the loss of human capital specific to their former industry remains as an important hurdle to recovery.
Keywords: F16; F66; J60; J24; J31; L67; 330; workers' adjustment to trade shock; globalization; earnings trajectories; specific human capital; job mobility; unemployment; low-wage country competition; multi-fibre arrangement; China